Perbedaan Perkembangan Sosial Anak Usia 3-6 Tahun Dengan Pendidikan Usia Dini Dan Tanpa Pendidikan Usia Dini Di Kecamatan Peterongan Jombang - Wulandari, Retno (2016)
Background. Growth and development of children is influenced by many factors, including the stimulation of the development of the child and environmental factors. Early childhood education is a form of stimulation that is basically intervention efforts that create the environment for early childhood in order to stimulate all aspects of child development. Method. This study was observational analytic with cross sectional approach. The sampling technique of random sample (probability samples) with a cluster sampling approach. The used statistical test Chi-Square test (expected values <5, maximal 20% of the number of cells). Results. Results of Chi-Square p value of 0.002 (p <0.05), there are differences in social development in children aged 3-6 years with early education and without early education. Because the so-called significant when p <0.05 (<5%). Conclusion. Based on the results of the study conducted by researchers, p value of 0.002 (p <0.05), there are significant differences between social development in children aged 3-6 years with early childhood education and without early childhood education in Peterongan Sub District Jombang.